In vivo evidence for long-term vascular remodeling resulting from chronic cerebral hypoperfusion in mice. Issue 2 (February 2017) - Struys, Tom; Govaerts, Kristof; Oosterlinck, Wouter; Casteels, Cindy; Bronckaers, Annelies; Koole, Michel; Van Laere, Koen; Herijgers, Paul; Lambrichts, Ivo; Himmelreich, Uwe; Dresselaers, Tom
We have characterized both acute and long-term vascular and metabolic effects of unilateral common carotid artery occlusion in mice by in vivo magnetic resonance imaging and positron emission tomography. This common carotid artery occlusion model induces chronic cerebral hypoperfusion and is therefore relevant to both preclinical stroke studies, where it serves as a control condition for a commonly used mouse model of ischemic stroke, and neurodegeneration, as chronic hypoperfusion is causative to cognitive decline. By using perfusion magnetic resonance imaging, we demonstrate that under isoflurane anesthesia, cerebral perfusion levels recover gradually over one month. This recovery is paralleled by an increase in lumen diameter and altered tortuosity of the contralateral internal carotid artery at one year post-ligation as derived from magnetic resonance angiography data. Under urethane/α-chloralose anesthesia, no acute perfusion differences are observed, but the vascular response capacity to hypercapnia is found to be compromised. These hemispheric perfusion alterations are confirmed by water [ 15 O]-H2 O positron emission tomography. Glucose metabolism ([ 18 F]-FDG positron emission tomography) or white matter organization (diffusion-weighted magnetic resonance imaging) did not show any significant alterations. In conclusion, permanent unilateral common carotid artery occlusion results in acute and long-term vascular remodeling, which may have immediate consequences for animal models of stroke but also vascular dementia.